(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the issues of forming legal immunity against factors that have a negative impact on the legal education of young people, respect for laws and rules of etiquette, loyalty to national values, and a comprehensive approach to the work of instilling a sense of intolerance towards offenses in each person are highlighted. Young people are an integral part of any society, and in the era of globalization, its problems are the first to emerge, the global problems of humanity, the real processes and forms of globalization, the youth parameter is the first place, it is the youth who suffer from the economic and social side and are at the center of conflicts. they can go and stay. First of all, it was stated that young people should learn to live on the basis of modern secular ethics.